MENINGKATKAN KEMAMPUAN MENULIS BERITA SISWA KELAS IX SMP JALAN JAWA MELALUI PEMBELAJARAN “KOMEDO” - Isani Kulup, Luluk (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
The aim of this research is to increase students of Grade 9 SMP Jalan Jawa ability to write news through KOMEDO learning. Based on the result of the study, it is known that the mean score of students’ ability to find news in preliminary condition is 58.14 and in cycle 1 it reached 75.03. It means that there is a 16.89 increase. From cycle 1 to cycle 2, there is an increase of mean score from 75.03 to 85.64. It means that the mean score of students’ ability to write news increased 10.61 points. There are an increase in the level of mastery learning achievement of Minimum Criteria of Mastery in the preliminary conditions to cycle 1 and from cycle 1 to cycle 2.